Optoelectrical anisotropy in graphene oxide supported polythiophene thin films fabricated by floating film transfer - Pandey R.K.; Tripathi A.S.M.; Pandey S.S.; Prakash R. (My University, 2025)
A facile method for the fabrication of highly oriented hybrid thin films of conjugated polymer (CP) with graphene oxide (GO) as 2D nano-filler over the high surface tension liquid substrate by floating film transfer is being reported. Formation of the self-assembled oriented hybrid thin film has been validated using multiple characterization techniques. Hybrid thin films thus prepared have been used for the fabrication of organic field effect transistors (OFETs) followed by investigation of anisotropic charge carrier transport. OFETs made with hybrid films oriented in channel direction exhibited the superior device performance with >6 fold augmentation in field effect mobility (μ) and one order improvement in on/off ratio as compared to that of devices based on pristine CP. However, pristine polymer shows 2.2 fold enhancement in mobility and one order augmentation in on/off ratio in parallel orientation as compared to the corresponding perpendicularly oriented films. Thus, our study has elucidated a path to obtain oriented, aligned, and self - assembled hybrid films for further improvement in the device performance aiming towards the applications in organic electronics. © 2019